Research Article: Survival Analysis of Under Five Mortality in Rural Parts of Ethiopia - Seyoum, Yared; Sharma, M.K. (International Journal of Statistics in Medical Research, 2014)
Child mortality is a factor that is associated with the well-being of a population and it is taken as an indicator of health development and socioeconomic status. According to the 2011 UN report during the last 10 years, the death rate for children under five has decreased by 35% worldwide. UNICEF in 2008 reported that Ethiopia has reduced under-five mortality by 40 percent over the past 15 years. From the EDHS 2011 report child mortality rate in Ethiopia was reduced from 50/1000 deaths in 2005 to 31/1000 deaths in 2011. The Ethiopian Demographic and Health Survey data are used for the study. In this paper we have attempted to find out the impact of socioeconomic, demographic and environmental factors in the context of under five mortality. In this attempt we first analyzed our data using Kaplan-Meier non-parametric method of estimation of survival function and also using lifetable. We have also used Log-Rank test to compare different survival functions and found that sex, type of birth, religion, mothers’ education, birth order, maternity age, source of drinking water and region have statistically significant difference in the under five survival time. We have also used Cox proportional hazard model to identify the covariates which influence the under five mortality. But we found that our data do not fulfill the proportionality assumption of Cox proportional model in case of infant and child mortality. Then we applied stratified Cox proportional model to our data to find out the potential covariates which influence under five mortality and found birth order, mothers’ education level, sex, type of birth and the interaction of birth order and sex as vital factors for the deaths occurring under the age of five. The Cox proportional hazard models which were used separately for each stratum also identified mothers’ educational level, sex, type of birth, and the interaction of sex and water supply as the risk factors for the death of infants. Whereas for child stratum; type of birth, mothers’ education, sex and the interaction of water supply and sex were the risk factors associated with the death of children.